Factors associated with the outcome of open tibial fractures - Mohd Yusof, Nazri; Khalid, Kamarul Ariffin; Zulkifly, Ahmad Hafiz; Zakaria@Mohamad, Zamzuri; Mohammad Amin, Mohammad Azril; Awang, Mohd Shukrimi; Che Ahmad, Aminudin; Akter, Sheikh Farid Uddin (Universiti Sains Malaysia, 2013)
Background: Although open tibial fractures are common in Malaysia, the outcomes for these patients have not been evaluated in the literature. This retrospective study was conducted to examine the factors associated with infection and non-union in open tibial fractures managed at Hospital Tengku Ampuan Afzan (HTAA), Kuantan, in 2009. Methods: From 1 January until 31 December 2009, the Department of Orthopaedics of HTAA managed 58 patients with open tibial fracture who had a minimum of a one year follow-up period. The median age was 24.5 years (range: 4 to 72 years). The open tibial fractures were graded using the Gustilo open fracture classification as follows: 4 grade I, 21 grade II, 24 grade IIIA and 9 grade IIIB. All open fractures were subjected to a standard treatment protocol at HTAA, which includes the use of prophylactic antibiotics, emergency debridement, fracture stabilisation, wound coverage, and bone reconstruction when required. The mean time from injury to the initial debridement was 29.7 hours (range: 13 to 216 hours). Results: Seventeen (29%) cases were complicated by infection, and 10 patients (17%) developed non-union. The grade of the open fracture was significantly associated with infection, and age and the time interval between the injury and the initial wound debridement were significantly associated with non-union. Conclusions: The high rates of infection and non-union, particularly in severe open fractures, indicate that there is a need to improve the management of open tibial fractures treated at HTAA. The time to initial debridement is an important factor that can be readily amended to improve the outcome. Further studies with larger sample sizes are likely needed to replicate and confirm our findings. Keywords: assessment, case management, fractures, open, patient outcome, tibia